مقاصد شریعت میں علامہ عزالدین بن عبدالسلامؒ کے افکار کا منفرد تجزیہ: The Unique Analysis of ’Allāmah ʿIzz al-Dīn Ibn ʿAbd al-Salām’s Thoughts on the Objectives of Sharī’ah - Hafiz Masood ur Rahman khan; Syed Syar Ali Shah; Muhammad Usman Fateh Muhammad (International Research Journal of Arabic and Islamic Studies, 2024)
This study explores the new dimensions of Maqāṣid al-Sharīʿah (objectives of Islamic law) through a specialized examination of the thoughts of contemporary Muslim thinkers. It investigates how these scholars have interpreted and expanded upon the classical understanding of Maqāṣid, offering fresh perspectives that address modern challenges and contexts. The research highlights the innovative approaches taken by these thinkers in reinterpreting Islamic legal principles to align with current societal needs while remaining faithful to Islamic tradition. By analyzing these contributions, the study aims to provide a comprehensive understanding of the evolving discourse on Maqāṣid al-Sharīʿah.